2016
DOI: 10.4103/0970-0218.177523
|View full text |Cite
|
Sign up to set email alerts
|

Burden of ocular motility disorders at a Tertiary Care Institution: A case to enhance secondary level eye care

Abstract: Aim:To evaluate the profile of strabismus and amblyopia in patients presenting to a tertiary care institution in order to understand the disease burden.Materials and Methods:A retrospective, prospective hospital-based observational study was conducted at a tertiary level eye care hospital in India. All patients with strabismus or amblyopia who presented over a 1-year period were identified and referred to the squint clinic, where they were evaluated with a detailed clinical history and examination.Results:A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…[ 13 ] In a hospital-based study conducted in North India, 6.9% of the study population of 24,475 patients had strabismus. [ 19 ] Following age stratification, the authors noted that 14.8% of patients aged up to 12 years had strabismus, which was greater than in our study (4.95%). [ 19 ] Previous hospital-based studies from other parts of the world have reported a higher prevalence of strabismus, including 17.9% in Ethiopia and 22% in Cameroon.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…[ 13 ] In a hospital-based study conducted in North India, 6.9% of the study population of 24,475 patients had strabismus. [ 19 ] Following age stratification, the authors noted that 14.8% of patients aged up to 12 years had strabismus, which was greater than in our study (4.95%). [ 19 ] Previous hospital-based studies from other parts of the world have reported a higher prevalence of strabismus, including 17.9% in Ethiopia and 22% in Cameroon.…”
Section: Discussionmentioning
confidence: 42%
“…[ 19 ] Following age stratification, the authors noted that 14.8% of patients aged up to 12 years had strabismus, which was greater than in our study (4.95%). [ 19 ] Previous hospital-based studies from other parts of the world have reported a higher prevalence of strabismus, including 17.9% in Ethiopia and 22% in Cameroon. [ 20 , 21 ] The prevalence is marginally higher than the rates reported in other multi-ethnic population-based studies such as the MultiEthnic Pediatric Eye Disease Study (MEPEDS) from the USA (African Americans and Hispanics: 2.5%; Asians and non-Hispanic whites: 3.24%), the Strabismus, Amblyopia, and Refractive Error in Singaporean Children Study (STARS) from Singapore (0.8%), the Baltimore Pediatric Eye Disease Study (BPEDS) from the USA (Whites: 3.3%; African Americans: 2.1%) and from the UK (2.4%), Australia (2.8%), Brazil (1.4%), and Japan (1.28%).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…after getting recognized as contributing factor in vision loss and impaired binocular function in children, it has been given due attention, in the recent thrust on paediatric ophthalmology in the Vision 2020 initiative. 5 Strabismus causes grave ocular dysfunction including double vision, eyestrain, vision loss, poor depth perception as well as cosmetic stigma among patients. Psychosocial difficulties relating to socially noticeable strabismus persist into teenage and adult years.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published study from our centre has shown the overall magnitude of strabismus to be 6.9% among the patients visiting the outpatient department. [ 1 ] Hence, strabismus surgery constitutes a sizeable number of the commonly performed ophthalmic surgeries. The most common causes of reoperations in strabismus include an overcorrection or an undercorrection.…”
mentioning
confidence: 99%